(untitled) (International Seven Journal of Health Research, 2023)
Chronic Obstructive Pulmonary Disease (COPD) and asthma are common respiratory diseases, but with complicated definitions. Spacers are devices used for the administration of inhaled medications, aiming to reduce the need for synchronization by the patient, allowing him/her to breathe normally during the administration of the medication. However, due to high cost and low availability, the use of commercial spacers is hampered in developing countries, such as Brazil. To solve this problem, several forms of homemade spacers have been developed. This project aims to expand knowledge on the main lung diseases seen in primary health care and their interventions based on the latest evidence and outpatient therapeutic updates, including the use of home-made inhaler devices. The aim is to promote adherence to inhalation treatment and improve patients’ quality of life. The rationale for this project is that the use of spacers facilitates adherence to inhaled medication treatment for asthma and COPD, as well as for patients who have both conditions. The project aims to provide spacers for all patients who use this type of medication, respecting the principles of universality, equity and equality of the Unified Health System. The method used was an intervention project carried out in the health strategy from 05/25/2021 to 07/02/2021. Homemade spacers were manufactured using 500mL PET bottles, both in the adult and pediatric models. The spacers were distributed along with user manuals and guidance on the importance of asthma treatment. Users were randomly selected using a search for patients using the medications salbutamol spray and beclomethasone spray. The results of the project were positive, with the spacers being made and delivered within the stipulated time. This contributed to a better administration of inhalation drugs, enabling a better control of the diseases analyzed and optimizing the treatment of users. In conclusion, the method of administration of inhaled drugs using a spacer reduces oral deposition and optimizes the inhalation of particles of adequate size. There was a good response from users and adherence to treatment with the offer of homemade spacers, in addition to a correlation between the improvement of the profiles of users served in the ESF.